433 ELEVATED DEOXYPYRIDINOLINE/PYRIDINOLINE RATIOS IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1 SUGGEST ABNORMALITY OF BONE REMODELING RATHER THAN COLLAGEN BREAKDOWN FROM OTHER TISSUES. Issue 1 (1st January 2007) - Stevenson, D. A.; Schwarz, E. L.; Viskochil, D. H.; Moyer-Mileur, L. J.; Murray, M.; Firth, S.; D'Astous, J. L.; Carey, J. C.; Pasquali, M.
Abstract : Objective: Neurofibromatosis type 1 (NF1), although classically thought of as a neurocutaneous disorder, is associated with localized skeletal abnormalities, including long-bone dysplasia, scoliosis, sphenoid wing dysplasia, and bone cysts. Our preliminary studies have documented decreased bone mineral density in children with NF1. Pyridinium cross-links [pyridinoline (Pyd) and deoxypyridinoline (Dpd)] are hydroxylysine-derived cross-links of mature collagen excreted in urine as a result of collagen degradation. Both Pyd and Dpd are found in bone and cartilage, but Dpd is most abundant in bone and reflects more the status of bone. To draw inferences of bone resorption, studies were designed to assess the Dpd/Pyd ratio in individuals with NF1 compared with individuals without NF1. Methods: The total (free plus peptide-bound) pyridinium cross-links from two consecutive first morning urines from 60 NF1 children (ages 5-19) were extracted after acid hydrolysis and analyzed by high-performance liquid chromatography. Data were compared with 99 healthy controls without NF1. Regression analysis controlling for age and skeletal dysplasia status (defined as scoliosis, long-bone dysplasia, and/or sphenoid wing dysplasia) was used. Results: Statistically significant increases of Pyd ( p = .019) and Dpd ( p < .001) were observed in individuals with NF1. The Dpd/Pyd ratio was elevated in individuals with NF1 ( p < .001). This Dpd/Pyd ratio was increased by 32% compared with controls. Conclusions: The elevated urinary excretion of pyridinium cross-links, both Dpd and Pyd, reflects increased collagen degradation in children with NF1. In addition, the elevated Dpd/Pyd ratio shows that the increased collagen breakdown products are predominantly due to abnormal resorption of bone and not from collagen breakdown of other tissues. The linear regression analysis adjusting for skeletal dysplasia status suggests that NF1 haploinsufficiency contributes to increased bone resorption and a generalized abnormality of bone remodeling predisposing individuals with NF1 to localized skeletal defects.